La Grèce, pays d’accueil et d’exil des Grecs dans la dramaturgie grecque du xxe et xxie siècle - Athanassios Blessios (Cahiers Balkaniques)
The subject of Greece as a country of reception and of exile for the Greeks is quite sufficiently utilized by the Greek dramaturgy of the 20th and 21st century. The plays And from Smyrna... to Thessaloniki by Mini Ntenissi, (The) Alive dead by Chryssanthos Gaios, Exile by Pavlos Matessis, The diary of the sand by Dimitris Kordatos, as also others, demonstrate this special interest of the authors. The authors emphasize the adaptation in the Greek society of the refugees, the immigrants, the expatriates, the people who have suffered a political exile in their own country, which is facilitated by the natives. Nevertheless, their mental course is also important, as their regrettable experiences can lead to their mental destabilization, to antisocial actions or to their isolation by the society. Finally, their adaptation depends more on their desire and aptitude to be incorporated in the society than on the society itself.